Up, down, and sideways : anthropologists trace the pathways of power - Stryker, Rachael, 1972-; González, Roberto J. (Studies in public and applied anthropology., 2016)
Using a "vertical slice" approach, anthropologists critically analyze the relationship between undemocratic uses and abuses of power and the survival of the human species. The contributors scrutinize modern institutions in a variety of regions--from Russia and Mexico to South Korea and the U.S. Up, Down, and Sideways is an ethnographic examination of such phenomena as debt culture, global financial crises, food insecurity, Indigenous land and resource appropriation, the mismanagement of health care, and corporate surrogacy within family life. With a preface by Laura Nader, this is essential reading for anyone seeking solid theories and concrete methods to inform activist scholarship